Implementasi Evaluasi Pembelajaran Berbasis Digital di Sekolah Dasar - Agresia Desti; Nazumi Anggofi; Siti Aisyah; Desclarista Salwa Putri; Muhamad Arif Alfa Rizi; Ranti Meizatri; Muhammadi Muhammadi (Journal Innovation In Education, 2025)
This study aims to describe the implementation of digital-based learning evaluation in elementary schools and analyze its implementation in supporting the learning process. The study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews with teachers, and documentation. The research was conducted in four elementary schools, namely SD Binekas Bandung, SD Negeri 14 Siguntur Muda, SD Negeri 29 Siguntur Muda, and SD Negeri 43 Siguntur Muda. The digital evaluation media used included Smart TV and Wordwall, which were utilized in the implementation of diagnostic and formative evaluations. The results showed that the implementation of digital-based learning evaluation was able to increase student engagement, active participation, and motivation to learn through the presentation of interactive questions and immediate feedback. In addition, digital evaluation helped teachers assess students' understanding in real time and adjust learning strategies according to student needs. However, the implementation of digital-based evaluation still faced technical obstacles, such as limited devices and supporting facilities. Overall, the implementation of digital-based learning evaluation is considered effective in supporting learner-centered learning and improving the quality of the evaluation process in elementary schools, with the proviso that there is a need to improve teacher competence and provide adequate digital facilities.